Changes in the rumen development, rumen fermentation, and rumen microbiota community in weaned calves during steviol glycosides treatment - Wang, Kexin; Jiang, Maocheng; Chen, Yuhang; Huang, Yuncheng; Cheng, Zhiqiang; Datsomor, Osmond; Jama, Shakib Mohamed; Zhu, Liping; Li, Yajing; Zhao, Guoqi; Lin, Miao (Frontiers in Microbiology, 2024)
Early weaning leads to weaning stress in calves, which hinders healthy growth and development. As an excellent sweetener applied in food, steviol glycosides (STE) has also been shown to exhibit positive biological activity in monogastric animals. Therefore, this study aimed to evaluate the impact of incorporating STE as a dietary supplement on rumen development, fermentation, and microbiota of rumen in weaned calves. This study selected 24 healthy Holstein bull calves and randomly allocated them into two groups (CON and STE). The results indicated that supplementation STE group improved rumen development in weaned calves, as demonstrated by a marked increase in the weight of the rumen, as well as the length and surface area of the rumen papilla. Compared with the CON group, the concentrations of total volatile fatty acids (TVFA), propionate, butyrate, and valerate were higher in the STE group. Moreover, STE treatment increased the relative abundance of Firmicutes and Actinobacteria at the phylum level. At the genus level, the STE group showed a significantly increased relative abundance of Succiniclasticum, Lachnospiraceae_NK3A20_group, and Olsenella, and a decreased relative abundance of Acinetobacter compared to the CON group. Pusillimonas, Lachnospiraceae_NK3A20_group, Olsenella, and Succiniclasticum were significantly enriched in rumen chyme after supplementation with STE, as demonstrated by LEfSe analysis. Overall, our findings revealed that rumen bacterial communities altered in response to the dietary supplementation with STE, and some bacterial taxa in these communities may have positive effects on rumen development during this period.